GP73 level in patients with chronic hepatitis B: Relationship with liver biopsy, levels of ALT, AST and HBV DNA - Aynur Atilla; Mehmet H Taşkın; Zülay Kazak; Saliha Aydın; S Sırrı Kılıç (Wolters Kluwer Medknow Publications, 2022)
Background/Aims: In this study, we investigated the Golgi protein 73 (GP73) level in Hepatitis B and determined the correlation between Hepatitis B virus (HBV) DNA, alanine aminotransferase (ALT), aspartate aminotransferase (AST) levels, and liver histopathology. Materials and Methods: GP73 levels were estimated by enzyme-linked immunosorbent assay in serum samples from patients. Liver biopsy specimens were examined by the same pathologist. Results: This study included a total of 127 patients who underwent liver biopsy. Of patients, 85% were HBeAg negative. HBV DNA level was median 134667 IU/mL (2247-170000000 IU/mL), Liver biopsy results revealed a mean Histological Activity Index (HAI) grade of 7.7 ± 3.4 and a mean fibrosis stage of 2.25 ± 1.06 gr/dL. GP73 was as follows: a mean of 14.8 ± 7.9 ng/mL and a median of 12.9 (4.8-50.1) ng/mL. A weak correlation between GP73 level and AST (r = 0.236, P = 0.11), fibrosis stage (r = 0.287, P = 0.002), and HAI grade (r = 0.218, P = 0.016) was noted. No statistically significant correlation was detected between GP73 and ALT (r = 0.16, P = 0.08), HBV DNA (r = 0.13, P = 0.08). Conclusion: Although recent studies revealed a strong correlation and increased GP73 levels in accordance with HAI scores and the fibrosis grade of liver, we detected a weak correlation between serum GP73 levels and HAI scores, fibrosis stage, and AST. This may be due to the insufficient number of patients with higher HAI grading and fibrosis staging in our study. Therefore, we concluded that, in cases of low-moderate fibrosis and HAI grading, GP73 seemed not to be useful and a reliable marker to replace liver biopsy.